2016
DOI: 10.1093/alcalc/agw053
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Liver Stiffness Using Transient Elastography in Alcoholic Patients Following Abstinence

Abstract: We prospectively evaluated liver stiffness by Fibroscan in patients with alcohol-related liver disease at baseline and following abstinence. After 1 month of abstinence, the LS is dramatically reduced, especially when values are greater than 7 kPa and transaminase elevated at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…18 Such decreases are more marked in patients remaining abstinent after initial detoxification. [10][11][12] Our study combined a prospective follow-up evaluation of LS with clinical and biological data and liver histology. TE was performed after a median of 6 days of abstinence, making it plausible that LS already had decreased in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Such decreases are more marked in patients remaining abstinent after initial detoxification. [10][11][12] Our study combined a prospective follow-up evaluation of LS with clinical and biological data and liver histology. TE was performed after a median of 6 days of abstinence, making it plausible that LS already had decreased in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, the thresholds determined for severe fibrosis or cirrhosis have varied and are substantially higher than for other etiologies. LS decreases rapidly in patients with alcohol withdrawal, [10][11][12][13][14][15] but no prospective study has correlated histology and TE follow-up evaluation…”
mentioning
confidence: 99%
“…Some authors have pointed out that steatohepatitis may lead to overestimation of liver fibrosis[ 54 ]. The risk of overestimation especially applies in patients who are abstinent, as liver stiffness decreases with cessation of alcohol use, especially with baseline values higher than 7 kPa[ 55 ].…”
Section: Non-invasive Methods For Assessment Of Liver Damagementioning
confidence: 99%
“…A study found elastography provided an assessment of fibrosis that was comparable to liver biopsy [16]. Other authors, however, have expressed concerns that alcohol-related steatohepatitis may distort results, leading to overestimation of liver fibrosis in this population [54], especially in patients who maintain abstinence from alcohol, as liver stiffness seems to dramatically decrease with cessation of alcohol use [55].…”
Section: Transient Elastographymentioning
confidence: 99%